DESCRIPTION OF TARGET LEARNERS - Abdullayeva Firuza; Sanjar Djalalov (PEDAGOGS, 2024)
Abstract: In the article it is discussed about the types of target learners’ description. The article consists of abstract, basic concepts, introductory part, main body, conclusion and used literature.